Voluminous magma formation for the 30-ka Aira caldera-forming eruption in SW Japan: contributions of crust-derived felsic and mafic magmas - Nishihara, Ayumu; Tatsumi, Yoshiyuki; Kaneko, Katsuya; Kimura, Jun-Ichi; Chang, Qing; Geshi, Nobuo; Miyazaki, Takashi; Vaglarov, Bogdan Stefanov; Hinata, Hironobu; Suzuki-Kamata, Keiko (Frontiers in Earth Science, 2024)
Understanding the origin, assembly, and evolution of voluminous magma that is erupted in catastrophic caldera-forming eruptions (CCFEs) is a community imperative. A CCFE of the Aira caldera at 30 ka discharged over 350 km3 of magmas that can be grouped into petrographically and geochemically distinct types: voluminous rhyolite, small amounts of rhyodacite, and andesite magmas. To further understand the magma plumbing system of the Aira CCFE, we examined geochemical characteristics of whole rock and plagioclase from its eruptive deposits. The trace element and 87Sr/86Sr signatures recorded in the plagioclase phenocrysts of these magmas indicate that the three magmas were originally produced by partially melting an identical source rock, which was estimated to be a mafic amphibolite with 87Sr/86Sr of ~0.7055 that comprises the lower crust. Melting of mafic amphibolite produced both felsic and mafic magmas by low- and high-degrees of partial melting, respectively. The mafic magma assimilated uppermost crustal materials and crystallized to produce an andesite magma type. The andesitic magma consists of phenocrysts (~39 vol.%) and melt with a dacitic (~70 wt% SiO2) composition. The felsic magma mixed with the andesite magma of ~10% and crystallized, forming the rhyolite magma. The mixing between the andesite and rhyolite magmas before the Aira CCFE produced the rhyodacite magma. The 30 ka Aira CCFE magmas were generated only by melting two kinds of crustal materials with different geochemical characteristics and had geochemical variations due to different conditions of partial melting and mixing between various crustal melts. The lack of definitive evidence that the mantle component mixed with the Aira CCFE magmas suggests that the mantle-derived magmas worked only as a heat source for crustal melting.